Parameters of two-channel five-zone dielectric structure for experiments on wakefield acceleration in KIPT - Zaleskyi, D.Yu.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2018)
The computations results of the parameters of a two-channel five-zone rectangular dielectric structure for the experimental test of basic principles of using such structures for wakefield acceleration are presented. The structure consists of two adjacent vacuum channels (one for the drive bunches, the other for the accelerated bunch) bordered by dielectric slabs. The entire structure is placed in a rectangular waveguide. In the work is also investigated the tolerances for parameters of the structure that affect the value of the transformer ratio and the accelerating gradient.